SECTION ON INHERITANCE RIGHTS OF DIFFERENT RELIGION CHILDREN IN INDONESIA NATIONAL LEGAL PERSPECTIVE - Idrus M. Said; Asbar Tantu; Rugaiya (Novateur Publications, 2023)
he prevalence of interfaith marriages in Indonesia has resulted in complicated and difficult legal implications in disputes over Islamic civil law in Indonesia. Among the implications of the legal issues that occur are children's inheritance rights as a result of interfaith marriages by both parents. Therefore this paper aims to examine, related to the inheritance rights of children of different religions from the perspective of positive law and Islamic law in Indonesia as unification law in the national legal order in Indonesia, as a legal system (the legal system) which works as a means of social control or work as a means of maintaining social order in the midst of a plurality of religions, cultures, ethnicities and customs, as well as the dynamic polarization of social relations. In this study the authors used qualitative methods with the aim of developing knowledge through exploration between proving and discovering the law of inheritance rights for children of different religions from the perspective of positive law and Islamic law as laws that are unified in the Indonesian national legal order. Through a phenomenological and juridical-normative approach, the purpose of using this approach is that the author uncovers and finds data from interfaith marriage events on children's inheritance rights, as well as interpretations of several grounded theories as a means of exploration to prove and find legal inheritance rights for children as a result of their parents' marriage. different religions. The next step the writer did comparative approach to the content discussed from data and reading literature which is a source of primary and secondary data with the aim of comparing it to then be descriptive from inductioninterpretation to deduction-interpretation, so as to be able to provide a description of the focus of the problem with concrete explanations. From the data and the results of reading the data sources, it is imperative for the author to use or make a literal interpretation, namely legal discovery which is carried out by explaining the texts of legal arguments whether to get or not to get the inheritance of children of different religions in the perspective of positive law and Islamic law which unification into the Indonesian national legal order. The types of data in this paper include primary data sources, namely from laws, government regulations, legal books, legal journals, research results and jurisprudence that have permanent legal force in cases of children's inheritance rights due to the difference in the religion of their parents. The data collection technique was taken by means of document studies (literature review), namely collecting primary data sources that explain the inheritance law system for children of different religions from the perspective of positive law and contemporary Islamic law. While the data analysis techniques in this paper include: data reduction, data presentation, data verification, and data validity testing
Keywords: Inheritance Rights; Children Different Religion; Indonesian National Legal Prespektif